Evaluasi Penggunaan Human Serum Albumin Pada Pasien Penyakit Dalam Di Rumah Sakit Imanuel Way Halim Tahun 2022 - Septilia, Riska; Perangin Angin, Martianus; Samor, Vania Amanda (Peneliti.net, 2024)
Human serum albumin is a plasma expander product that has been used extensively to treat hypovolemia and correct hypoalbuminemia and is always indicated in conditions of albumin deficit or what is known as hypoalbuminemia accompanied by hypovolemia due to fluid imbalance in the body. The aim of this study was to evaluate the use of human serum albumin in internal medicine inpatients at Imanuel Way Halim Hospital. This research was conducted in a descriptive analytic manner using a non-experimental retrospective method. The data were obtained from the medical records of inpatients who received albumin therapy at Imanuel Way Halim Hospital. The results showed that of the 30 internal medicine inpatients who received albumin therapy, the most patients were obtained, namely 17 male patients (57%) and 13 female patients (43%). There were 11 adult patients (37%) and 19 elderly patients (63%). Right dosage (100%), Right Indication (100%). The use of albumin in inpatients at the Immanuel Way Halim Hospital installation is according to indications and rational doses.